2021
DOI: 10.3389/fpsyg.2021.732445
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Capitals: How Task-Oriented and Guanxi-Oriented Psychological Capitals Lead to a Sustainable Workforce in Rural China

Abstract: Psychological capital (PsyCap) is documented to be positive in influencing employees’ behavior. However, little attention has been paid to its role in maintaining a sustainable workforce in underprivileged rural areas. Also less known is the complex relations between PsyCap and other consequence variables. Moreover, previous studies in this field did not adequately address the cross-cultural applications of positive resources, though many facets of PsyCap are culture related. To address the gaps, the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 88 publications
(119 reference statements)
1
3
0
1
Order By: Relevance
“…However, no significant differences between the groups were observed in hope, resilience, or overall psychological capital scores. These studies align with prior research on psychological capital in public [57,[106][107][108][109] and private [110][111][112][113][114][115][116][117][118][119] sectors. However, it is unclear why the employees in public and private sectors differed in self-efficacy and optimism, but they did not differ in hope, resilience, or overall psychological capital.…”
Section: Public Sector Employees Partially Differ In Their Psychologi...supporting
confidence: 84%
See 1 more Smart Citation
“…However, no significant differences between the groups were observed in hope, resilience, or overall psychological capital scores. These studies align with prior research on psychological capital in public [57,[106][107][108][109] and private [110][111][112][113][114][115][116][117][118][119] sectors. However, it is unclear why the employees in public and private sectors differed in self-efficacy and optimism, but they did not differ in hope, resilience, or overall psychological capital.…”
Section: Public Sector Employees Partially Differ In Their Psychologi...supporting
confidence: 84%
“…Numerous studies have confirmed that psychological capital and its interventions are related to reduced work-related problems, not to mention positive wellbeing and workrelated outcomes [96][97][98][99][100][101][102][103][104][105]. Research of the psychological capital in the public sector has evidenced its' numerous benefits [57,[106][107][108][109]. Similarly, the studies on psychological capital in the business, entrepreneurial, or marketing contexts demonstrated the added value of psychological capital and its interventions for the private sector organizations [110][111][112][113][114][115][116][117][118][119].…”
Section: Psychological Capitalmentioning
confidence: 99%
“…Conflicts are inherent in team dynamics. Researchers grouped conflicts into taskoriented and interpersonal conflicts, with the former having positive impacts on team performance and the latter having negative impacts [40,41]. Task-oriented conflicts were raised in the study when students had different perceptions of the requirements of group assignments.…”
Section: The Barriers Preventing the Development Of Effective Teamsmentioning
confidence: 99%
“…Halihazırda pozitif psikolojik sermayenin öz yeterlilik, umut, iyimserlik ve dayanıklılık alt boyutlarına dahil edilecek olan pozitif yapıların mevcut alt boyutlarla nasıl ilişkili olduğunu keşfetmek, sadece pozitif psikolojik sermaye anlayışını zenginleştirmekle kalmaz, aynı zamanda diğer pozitif yapılar hakkındaki anlayışı da zenginleştirir. Pozitif psikolojik sermaye yapısına şimdi veya gelecekte eklenebilecek teori temelli, araştırılabilir, geçerli ölçüm araçlarına sahip, biçimlendirilebilir, geliştirilebilir ve performans ile ilişkili pozitif yapılar ise; bilgelik, yaratıcılık, akış deneyimi, öznel iyi oluş, mizah anlayışı, duygusal zekâ, minnettarlık, bağışlayıcılık, otantiklik, maneviyat ve cesaret kavramlarıdır (Guojuan, Shuling ve Junli, 2010;Luthans vd., 2007b;Xu, Wei, Liu ve Zhou, 2021;Zhao ve You, 2021). Pozitif psikolojik sermaye kavramına eklenebilecek pozitif yapılara ait sınıflandırma ve kavramların pozitif psikolojik sermaye içeriğine dâhil edilmesi için sahip olması gereken özellikler Tablo 1'de verilmiştir.…”
Section: Potansiyel Ve Gelecekteki Boyutlarunclassified
“…Exploring how positive constructs that will currently be included in the self-efficacy, hope, optimism, and resilience sub-dimensions of psychological capital relate to existing sub-dimensions enriches not only the understanding of psychological capital but also enriches the understanding of other positive constructs. Positive structures that can be added to psychological capital structure now or then, which are theory-based, researchable, having # Valid measurement tools, open to the formation and development, and related to performance are the followings concepts; wisdom, creativity, flow, subjective well-being, humour, emotional intelligence, gratitude, forgiveness, authenticity, spirituality, and courage (Guojuan et al, 2010;Luthans et al, 2007b;Xu et al, 2021;Zhao & You, 2021).…”
Section: Extended Abstractmentioning
confidence: 99%